EVALUASI PROGRAM KEAGAMAAN DALAM MENINGKATKAN KARAKTER RELIGIUS PESERTA DIDIK DI SDIT ALAM BINA INSANI MENGGUNAKAN MODEL CIPP - Rini Astuti; Basukiyatno; Suriswo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of religious programs in shaping students’ religious character at SDIT Alam Bina Insani using the CIPP (Context, Input, Process, Product) model. A mixed-methods approach was adopted, combining qualitative and quantitative data from interviews, observations, documentation, and questionnaires. The findings indicate that the program aligns with the school’s vision, is supported by competent teachers and adequate facilities, is carried out systematically, and results in significant behavioral improvements. The regression analysis revealed a very strong correlation (R = 0.995) and a determination coefficient of 0.990, indicating that 99% of the variation in religious character is influenced by the implementation of the religious program. These results underscore the importance of religious programs as integral to character development in Islamic-based schools.